Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/ppul.26076
|View full text |Cite
|
Sign up to set email alerts
|

Frequent hypoxemia found in infants with bronchopulmonary dysplasia after weaning home oxygen

Abstract: Objective Parental reports and brief clinical examinations are the primary information used to assist clinicians in weaning home supplemental oxygen in infants with bronchopulmonary dysplasia (BPD). Recorded nocturnal oximetry provides an objective assessment of hypoxemia; however, it is unknown if it identifies clinically undetected hypoxemia in the home setting. Our objective was to determine if nocturnal oximetry can identify unreported hypoxemia in infants with BPD who appear ready to wean from supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Other studies have demonstrated the utility of overnight oximetry studies as a modality of detecting the presence of hypoxemia in otherwise seemingly ready‐to‐be weaned off the oxygen 6 . The RHO trial conducted by Rhein et al regarding the use of oximetry studies in premature patients had earlier oxygen discontinuation compared to our cohort 20 .…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Other studies have demonstrated the utility of overnight oximetry studies as a modality of detecting the presence of hypoxemia in otherwise seemingly ready‐to‐be weaned off the oxygen 6 . The RHO trial conducted by Rhein et al regarding the use of oximetry studies in premature patients had earlier oxygen discontinuation compared to our cohort 20 .…”
Section: Discussionmentioning
confidence: 64%
“…At the time of NICU discharge, many patients with BPD have a need for home oxygen therapy. After discharge, this is monitored clinically or via assessments through overnight oximetry studies or polysomnograms (PSGs) based on institution and/or provider practice 5,6 . Reliance on clinical outpatient measures such as mean oxygen saturation (SpO 2 ), respiratory rate (RR), and brief clinical evaluations may underestimate underlying intermittent hypoxemia, particularly during sleep 5 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations